(untitled) (Proceedings of International Educators Conference, 2024)
The article examines linguistic and translation aspects within the English aviation terminology system. It explores methods for enriching English aviation terminology, conducts lexical-semantic and structural analyses, and discusses strategies for translating multi-component terms, abbreviations, and acronyms from aviation English into Russian.